Detention of Children as Security Threats under International Law - Fraz Ashraf Khan; Muhammad Hassaan Sohail (Journal of Religion and Society, 2025)
The detention of children deemed security threats in armed situations poses a difficult and little examined issue within international law. Notwithstanding established legal frameworks, including the Convention on the Rights of the Child and the Geneva Conventions, numerous children globally are incarcerated by state and non-state entities due to purported affiliations with armed groups or alleged involvement in hostilities. This practice prompts essential inquiries about the sufficiency of existing legal safeguards, the definition and extent of "security threat," and the alignment of detention procedures with the core principles of necessity, proportionality, and non-discrimination. Children in detention often endure severe conditions, insufficient access to legal aid, and minimal oversight, usually leading to infringements of their rights to due process, education, and rehabilitation. Furthermore, the stigmatization and suffering linked to detention hinder their reintegration into society and increase the likelihood of re-recruitment or radicalization. The paper explores a child protection methodology that emphasizes prevention, diversion, and alternatives to detention, consistent with international standards. It highlights the pressing necessity for research on governmental policies, accountability mechanisms, and the establishment of effective frameworks that harmonize genuine security concerns with the rights and welfare of the child. Rectifying these deficiencies is crucial for enhancing international legal adherence and safeguarding vulnerable children in conflict situations Keywords: Detention, Children, Security, Threats, International Law